Nonsurgical Treatment of a Massive Substance Loss - Pasquale Fino; Fioramonti Paolo; Diego Massera; Vittoria Amorosi; Maria Giuseppina Onesti (Case Reports in Medicine)
Traumatic wounds are caused by severe trauma, resulting in lesions with extensive skin and subcutaneous tissue loss and damage to tissue viability. A “difficult wound” is a solution of continuity that does not heal spontaneously within three months. The factors that determine it may be as follows: a massive loss of substance, an infection, the presence of foreign bodies, or the clinical condition of the patient. We report a case of a 25-year-old man that presents a skin lesion on the anterior region of the left arm with extensive necrosis of skin and subcutaneous plants that involve the underlying muscle planes, caused by a trauma due to a car accident. In most of the lesions of such size and position, there is always a need for surgery. But in this case, considering the young age and the regenerative capacity of the patient, a quick and targeted antibiotic therapy was chosen, combined with debridement and worked with collagenase ointment.